VALUASI EKONOMI KAWASAN WISATA PANTAI BALI LESTARI DI KABUPATEN SERDANG BEDAGAI, SUMATERA UTARA - Sitohang, Rosmeryana; Murniati, Ktut; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The goal of this study is to examine the variables that affect the number of visitors to Bali Lestari Beach as well as the beach's economic worth using trip cost data. A survey approach was employed in the study, and 77 respondents made up the sample. The trip cost approach was applied in this study. The research site, Bali Lestari Beach, was chosen consciously (on purpose). The period of time used to collect the data was from January–February 2022. The results of the study find that the average cost of travel to Bali Lestari Beach is IDR 139,580.36 per person. Among all travel expenses, additional charges constitute the highest share of total cost up to IDR 55,468 or 40 percent. The expense of travel, income, distance, and the availability of services and infrastructure all influence the number of visitors to Bali Lestari Beach. Bali Lestari Beach has an annual economic value of IDR 55,655,654,510, and each visitor has a consumer surplus of IDR 640,390. Keywords: consumer surplus, economic valuation, frequency of visits, tourist, travel cost.